2013
DOI: 10.1371/journal.pone.0083350
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis: Prognostic Value of Survivin in Patients with Hepatocellular Carcinoma

Abstract: BackgroundThe expression of survivin is a promising prognostic indicator for some carcinomas. However, evidence for the prognostic value of survivin with respect to survival in hepatocellular carcinoma remains controversial.AimTo conduct a systematic review of studies evaluating survivin expression in hepatocellular carcinoma as a prognostic indicator.MethodsThe relevant literature was searched using PubMed, EMBASE, and Chinese biomedicine databases, and two meta-analyses were performed. One studied the associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 36 publications
0
20
1
Order By: Relevance
“…One possible reason may be the lack of information on the molecular heterogeneity of the tumors being treated and consequently, making it difficult to interpret the overall biological response. Over-expression of survivin in HCC has been reported to correlate with poor prognosis [14]. In this study, we hypothesized that targeting survivin could be a treatment strategy for HCC and subsequently demonstrated the remarkable heterogeneity of expression of survivin and its phosphorylated active form (p-survivin) in HCC patients' tissues and cell lines.…”
Section: Introductionmentioning
confidence: 90%
“…One possible reason may be the lack of information on the molecular heterogeneity of the tumors being treated and consequently, making it difficult to interpret the overall biological response. Over-expression of survivin in HCC has been reported to correlate with poor prognosis [14]. In this study, we hypothesized that targeting survivin could be a treatment strategy for HCC and subsequently demonstrated the remarkable heterogeneity of expression of survivin and its phosphorylated active form (p-survivin) in HCC patients' tissues and cell lines.…”
Section: Introductionmentioning
confidence: 90%
“…First, an interruption of survivin levels plays an important role in reducing apoptosis of HCC. In agreement with this, several studies have concluded that survivin expression was correlated with poor prognosis in patients with HCC, and upregulation of survivin is an independent risk factor in hepatocellular carcinoma cell survival as well as in resistance to apoptosis (33). Second, and most importantly, survivinT34A increases arsenic trioxide-induced apoptosis.…”
Section: Discussionmentioning
confidence: 54%
“…Yu, et al found that the expression of BIRC5 was increased in LIHC tissues as compared to those adjacent nontumor samples and non-cancerous liver tissues (Yang et al 2011). Several articles demonstrated that BIRC5 expression correlated with unfavorable clinicopathological characteristics and predicted poor survivals in patients with LIHC (Augello et al 2009;Liu et al 2013;Ye et al PeerJ reviewing PDF | (2016:09:13329:1:1:NEW 5 Feb 2017)…”
Section: Discussionmentioning
confidence: 99%